Crealectics as a Creative Method: A New Approach to Holistic Innovation for Compossible Worlds - de Miranda, Luis (Palgrave Advances in Possibility Studies; Social Sciences; Social Sciences (R0), 2025)
This open access book introduces crealectics, a new creative methodology that bridges philosophical depth with practical innovation. Drawing on Leibniz's concept of compossibility – the idea that not everything possible can coexist in the same world –the author develops a five-phase approach to holistic innovation: resetting, crealing, profusing, compossibilizing, and realizing. Tested through real-world applications including case studies with Vattenfall R&D, the crealectic method offers an alternative to purely analytical or dialectical approaches to innovation, what the author calls “inner-novation." The book presents the C.I.P.H.E.R. model (Crealectic Intelligence and Philosophical Health for Enriched Realities), demonstrating how individual transformation and collective innovation can work together to create "the best of compossible worlds." This interdisciplinary work contributes to possibility studies, sustainability thinking, and innovation methodology, offering practical tools for academics, practitioners, and students seeking approaches to creative problem-solving that honor both diversity and coherence.